Factors associated with substance use treatment completion in residential facilities. (1st September 2015) - Mutter, Ryan; Ali, Mir M.; Smith, Kelley; Strashny, Alex
Highlights: Individuals in residential treatment for substance use often face many challenges. We analyzed factors associated with substance use treatment completion. Education, employment, and housing are associated with treatment completion. Private insurance is associated with treatment completion. Abstract: Purpose: Individuals in residential treatment often face many challenges, which can include limited education, unstable housing, difficulty participating in the workforce, and severe substance use problems. We analyzed factors associated with substance use treatment completion. We focused on factors that can be influenced by health care system changes resulting from the Affordable Care Act (ACA). Data and methods: We used the 2010 Treatment Episode Data Set – Discharges (TEDS-D), which is made available by the Substance Abuse and Mental Health Services Administration (SAMHSA). We analyzed factors associated with substance use treatment completion using logistic regression. Results: Individuals in residential treatment were often unemployed or not in the labor force, had prior substance use treatment episodes, used more than one substance, and were uninsured. Factors associated with treatment completion included older age, greater education, employment, criminal justice referral, not being homeless, and private insurance. Conclusion: The expansion in private insurance coverage as a result of the ACA may result in more treatment completion in residential settings. Changes to the Medicaid program resulting from the ACA, including coverage of substance use treatment as an essential health benefit and greater support for housing, education, and employment, may also contribute to more residential discharges ending in treatment completion.